2018
DOI: 10.1111/joor.12681
|View full text |Cite
|
Sign up to set email alerts
|

Association between chewing dysfunctions and temporomandibular disorders: A systematic review

Abstract: Temporomandibular disorder (TMD) is an umbrella condition presenting several signs and symptoms including pain in the temporomandibular joint (TMJ) and masticatory muscles, articular noises, earache, headache, irregular or restricted jaw function, chewing difficulty, and limited mouth opening. Such TMD impairment may cause disorders during the chewing process. Therefore, the purpose of this systematic review was to assess chewing dysfunctions measured by sEMG, and their association with TMD. A combination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
0
28
0
2
Order By: Relevance
“…Sieving of chewed natural or artificial food and following determination of the mean particle size is still thought to be the "gold standard" for the quantification of masticatory efficiency [49]. One of the other objective methods to assess the chewing process is surface electromyography but the results of the studies still have been controversial [50]. In conclusion, this cross-sectional study found that the global score of JFLS was the highest in patients with TMD with joint pain, followed by TMD with muscle-joint combined pain, muscle pain and TMD with internal derangement without pain.…”
Section: Correlations Between Jfls and Tmd Pain Painmentioning
confidence: 99%
“…Sieving of chewed natural or artificial food and following determination of the mean particle size is still thought to be the "gold standard" for the quantification of masticatory efficiency [49]. One of the other objective methods to assess the chewing process is surface electromyography but the results of the studies still have been controversial [50]. In conclusion, this cross-sectional study found that the global score of JFLS was the highest in patients with TMD with joint pain, followed by TMD with muscle-joint combined pain, muscle pain and TMD with internal derangement without pain.…”
Section: Correlations Between Jfls and Tmd Pain Painmentioning
confidence: 99%
“…A investigação de parâmetros polissonográficos foi realizada em alguns desses estudos, constatando uma relação entre DTM e dor na musculatura mastigatória e bruxismo do sono [9][10][11] . A literatura aponta que a musculatura mastigatória em indivíduos com bruxismo do sono realiza ações e demandas atípicas, podendo ocasionar alterações neuromusculares capazes de desencadear dor, cansaço e fadiga nesses indivíduos, com possíveis impactos no desempenho da função mastigatória 28 . Outro estudo evidenciou a presença de sonolência diurna excessiva em indivíduos com dor orofacial e com queixas de bruxismo do sono 13 , sendo esse um sintoma comum (sonolência) em indivíduos adultos com possíveis distúrbios do sono 29 .…”
Section: Discussionunclassified
“…While the use of EMG studies of the masseter and other masticatory muscles is well established in the management of TMJ and orofacial disorders, 19-21 fewer investigations have considered non-masticatory facial muscles. 16,22,23 Surface EMG has been proposed as a noninvasive method for exploring facial muscle function, especially in the fields of experimental psychology, 24 and rehabilitation after facial nerve palsy.…”
Section: Discussionmentioning
confidence: 99%